Ecological Constraints on the Evolution of Consumer Functional Responses - Amarasekare, Priyanga (Frontiers in Ecology and Evolution, 2022)
Intrinsically generated oscillations are a defining feature of consumer-resource interactions. They can have important consequences for the evolution of consumer functional responses. Functional response traits that can maximize resource (consumer) fitness ---low (high) attack rates and long (short) handling times --- generate high-amplitude oscillations that can predispose species to extinction during periods of low abundances. This suggests that the ecological consequences of consumer-resource oscillations may impede evolutionary outcomes that maximize fitness. Data suggest this to be a strong possibility. Time series analyses reveal consumer-resource cycles to be infrequent in real communities, and functional response studies show a preponderance of low attack rates and/or short handling times that preclude oscillations but maximize neither species' fitness. Here I present an eco-evolutionary model to address this tension between ecological dynamics and the evolution of functional response traits. I show that the empirically observed attack rate-handling time distributions emerge naturally from the interplay between individual-level selection and the population-level constraint of oscillation-induced extinction. Extinction at low abundances curtails stabilizing selection towards trait values that maximize fitness but induce large-amplitude oscillations. As a result, persistent interactions are those with low attack rates and/or short handling times. This finding suggests that differential persistence of genotypes with different attack rate - handling time combinations may act as an ecological constraint on the evolution of consumer functional responses. It emphasizes the importance of incorporating oscillation-induced extinction into models that link food web topology to community persistence.